Penurunan Tekanan Darah pada Penderita Hipertensi dengan Air Rebusan Biji Ketumbar - Besse Aulia Rahma; Wa Ode Sri Asnaniar; Suhermi; Akbar Asfar; Sudarman (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Hypertension is a cardiovascular disease that causes high death rates in the world. Hypertension that is not treated in the long term will cause more serious complications. One non-pharmacological treatment method uses herbal therapy, boiled water from coriander seeds. The aim of this research is to determine the effect of boiled coriander seed water on the blood pressure of hypertension sufferers in the Sajoanging Community Health Center working area. This research design uses a quantitative type of research with a quasi-experimental research design One-group pre-posttest design. The sampling technique is non-probability sampling using purposive sampling, that is, samples were taken from the population of hypertension sufferers in the Sajoanging Community Health Center working area who met the criteria of 30 respondents. Meanwhile, the analysis used was the frequency distribution test and the Wilcoxon statistical test with a significance level of ρ < α = 0.05. The results of the pre-test and post-test systolic blood pressure research given boiled water from coriander seeds showed a value of ρ = 0.001 ( ρ < α = 0.05). As well as pre-test and post-test diastolic blood pressure given boiled coriander seed water, the value obtained was ρ = 0.001 ( ρ < α = 0.05). The conclusion of this study proves that there is an effect of boiled water from coriander seeds on reducing systolic and diastolic blood pressure in hypertension sufferers in the Sajoanging Community Health Center working area, so that herbal therapy using boiled coriander seed water can be used as an alternative therapy for hypertension sufferers to control blood pressure.